A Multi Output Formulation for Analog Circuits using MOM-SVM - Shivalal Patro; Sushanta Kumar Mandal (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
This paper proposes performance based macro modeling of analog circuit using Multi Output Modeling (MOM) with the help of Support Vector Machine (SVM). SVM models the analog circuits and provides a relation between multi-input and multi-output parameters. In this work, Voltage Controlled Oscillator (VCO) is modeled as a test circuit which is designed in Cadence Virtuoso GPDK 45nm technology. From the Spice simulation results, the feasible dataset has been extracted from the complete dataset. Then, the VCO output frequency and phase noise is modeled by the width of the transistors which are the input parameters of the transistors. After tuning the model properly by k-cross validation method, the accuracy was found to be 96.1% which is good enough to make it use for the circuit synthesis purpose.